2018
DOI: 10.3389/fnbot.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

The Force Generation in a Two-Joint Arm Model: Analysis of the Joint Torques in the Working Space

Abstract: The two-segment model of the human arm is considered; the shoulder and elbow joint torques (JTs) are simulated, providing a slow, steady rotation of the force vector at any end-point of the horizontal working space. The sinusoidal waves describe the JTs, their periods coincide with that of the rotation, and phases are defined by the slopes of the correspondent lines from the joint axes to the end-point. Analysis of the JTs includes an application of the same discrete changes in one joint angle under fixation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Earlier, we suggested that the synergy of activation, reflecting the simultaneous activation of muscles belonging to different joints, might be closely related to the patterns of coincidence/opposition in the directions of the torques around the corresponding joints (Kostyukov, 2016; Tomiak et al, 2016; Gorkovenko, 2018; Kostyukov and Tomiak, 2018). Therefore, the existence might be proposed of a close relationship between the activation and force synergies.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Earlier, we suggested that the synergy of activation, reflecting the simultaneous activation of muscles belonging to different joints, might be closely related to the patterns of coincidence/opposition in the directions of the torques around the corresponding joints (Kostyukov, 2016; Tomiak et al, 2016; Gorkovenko, 2018; Kostyukov and Tomiak, 2018). Therefore, the existence might be proposed of a close relationship between the activation and force synergies.…”
Section: Discussionmentioning
confidence: 96%
“…The coinciding synergy relates to the similar modalities of the activated muscles at the joints (flexors and flexors; extensors and extensors), the opposing synergy matches combination of the different modalities (flexors and extensors; extensors and flexors). It has been shown theoretically that there is a strict prevalence of the coinciding synergy for isometric two-joint muscle contractions with complete circle turning of the end-point force vector within the working space (see Figure 6 in Kostyukov and Tomiak, 2018). The present study demonstrates experimentally the strong predominance of coincident synergy in real parafrontal movements produced in different parts of the working space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations